Designs and comparisons of authentication modules for IPSec in configurable and extensible embedded processor - Michail, Harris; Athanasiou, George S.; Makridakis, George (My University, 2010)
In this paper, a performance analysis of two alternative designs of SHA-1 hash function and a pure software version, implemented in a configurable and extensible embedded processor (Tensilica's Xtensa LX2) is presented. The first alternative is exploiting extensibility of incorporated platform; the second one is exploiting configurability and extensibility. These two alternatives are compared to the pure software implementation in the same processor. The results showed that exploiting both configurability and extensibility leads to high performance SHA-1 implementation. Up to 490% increase in terms of throughput is observed, while the area is significantly reduced by 28%. This work aims to offer base implementations for comparisons with future opts that authors are already working on.
Keywords: Cryptography; Lead; Embedded computer systems; Security